Neurodengue, a narrative review of the literature - Abelardo Queiroz Campos Araujo; Marco Antonio Lima; Marcus Tulius Teixeira Silva (Arquivos de Neuro-Psiquiatria)
Dengue fever (DF) is the most frequent arboviral disease globally. Deforestation, armed conflicts, and climate change have caused an unprecedented global spread of DF, raising concerns in healthcare systems worldwide. Systemic manifestations of the disease range from mild to severe and, in some cases, can lead to death. Although neurological complications have been reported over the last few decades, they are often neglected or underreported. The present narrative review aims to describe the most important central and peripheral nervous system complications and provide guidance to neurologists in terms of diagnosis and management.